2014
DOI: 10.1111/jcc4.12091
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Channel Use and the Role of Social Competence

Abstract: This study focused on channel complementarity among various interpersonal communication channels (face-to-face, telephone, e-mail, text messaging, and Facebook Dimmick, Kline, & Stafford, 2000;Ramirez, Dimmick, Feaster, & Lin, 2008), channel complementarity theory and related research suggest that increased use of newer communication technologies is associated with increased use (i.e., complementarity) of older communication technologies (e.g., Dutta-Bergman, 2004b) or face-to-face communication (e.g., Dutta-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Several studies have provided empirical support for this rationale: For example, in a study of 1,210 Dutch adolescents, students who spent more time using IMs also spent more time with their friends in offline contexts (Valkenburg & Peter, ). Next, people who write more e‐mails also write more text messages and use SNSs more actively (Ruppel & Burke, ). Similarly, Dutta‐Bergman () found that after 9/11, people who contributed to online support forums were also more likely to engage in offline support communities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Several studies have provided empirical support for this rationale: For example, in a study of 1,210 Dutch adolescents, students who spent more time using IMs also spent more time with their friends in offline contexts (Valkenburg & Peter, ). Next, people who write more e‐mails also write more text messages and use SNSs more actively (Ruppel & Burke, ). Similarly, Dutta‐Bergman () found that after 9/11, people who contributed to online support forums were also more likely to engage in offline support communities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Research related to mobilisation shows that use of mobile technology affords disadvantaged groups opportunities for cultural participation on their mobile devices (Chen, 2015). However, research supporting normalisation highlights that people with existing resource advantages (knowledge, material, networking, skills, or social, for example) tend to use the Internet or new technologies to enhance their network and social capacities, heightening the differences between themselves and with people who do not have either networking or technological competence (Ruppel and Burke, 2014).…”
Section: Information and Communication Capacity (Routinised Mobile Tementioning
confidence: 99%
“…For example, understanding the implications of relational talk about certain topics via technologies requires knowing how partners talk about those topics face-to-face (Caughlin & Sharabi, 2013). Further, use of one communication technology is often associated with the use of other communication technologies, and these associations can vary based on individual or relational factors (Ruppel & Burke, 2015;Ruppel, Burke, & Cherney, 2018). Despite the growing acknowledgement that communication technologies are embedded in the larger communication context of people's lives and relationships, over time, research has trended more toward studying specific technologies, such as social networking sites or video games (Borah, 2017).…”
mentioning
confidence: 99%